Lobe mediates Notch signaling to control domain-specific growth in the Drosophila eye disc. - Chern, J.J.; Choi, K.W. (Development, 2002)
Notch (N) activation at the dorsoventral (DV) boundary of the Drosophila eye is required for early eye primordium growth. Despite the apparent DV mirror symmetry, some mutations cause a preferential loss of the ventral domain, suggesting that the growth of individual domains is asymmetrically regulated. We show that the Lobe (L) gene is required non-autonomously for ventral growth but not dorsal growth, and that it mediates the proliferative effect of midline N signaling in a ventral-specific manner. L encodes a novel protein with a conserved domain. Loss of L suppresses the overproliferation phenotype of constitutive N activation in the ventral, but not in the dorsal eye, and gain of L rescues ventral tissue loss in N mutant background. Furthermore, L is necessary and sufficient for the ventral expression of a N ligand, Serrate (Ser), which affects ventral growth. Our data suggest that the control of ventral Ser expression by L represents a molecular mechanism that governs asymmetrical eye growth.